Lateral column lengthening versus subtalar arthroereisis for pes planovalgus in patients with cerebral palsy: a systematic review and meta-analysis - Chang-Hao Lin; Chun-Ho Chen; Chun-Ho Chen; Chun-Ho Chen; Shu-Hsin Yao (Frontiers Media S.A., 2024)
IntroductionAlthough pes planus, a common deformity in children with cerebral palsy (CP), is predominantly treated through lateral column lengthening (LCL), subtalar arthroereisis (SA) has also gained popularity for this purpose. This systematic review was conducted to compare surgical outcomes between LCL and SA for pes planovalgus in children with CP.MethodsPubMed, EMBASE, Cochrane Library, and Google Scholar were comprehensively searched for relevant articles reporting the outcomes of LCL and SA in the target population. Surgical outcomes were evaluated in terms of radiographic parameters and postoperative complications.ResultsThis review included 22 studies involving patients undergoing LCL (LCL group) and 9 studies involving those undergoing SA (SA group). LCL outperformed SA in terms of corrections in the talonavicular coverage angle (8.1°-42.1° vs. 8.0°-30.7°), anteroposterior talo-first metatarsal angle (12.3°-33.7° vs. 9.8°-21.4°), and calcaneal pitch angle (2.5°-29.7° vs. 3.5°-8.0°). Furthermore, the risk of postoperative complications, such as recurrence, pain, undercorrection, and overcorrection, was higher in the LCL group than in the SA group. However, the risks of reoperation and implant-related problems were higher in the SA group than in the LCL group. A meta-analysis of two randomized studies revealed that improvement in calcaneal pitch angle was significantly greater in the LCL group than in the SA group (mean difference: 2.09°; P = 0.0488).ConclusionLCL outperforms SA in correcting pes planus-related radiographic parameters in patients with CP. However, postoperative complications appear to be more common after LCL than after SA.Systematic Review Registrationhttps://inplasy.com/inplasy-2024-5-0126, Identifier 202450126.